Working with female offenders: a gender-sensitive approach - Van Wormer, Katherine S. (Wiley, 2010)
A gendered approach -- Traditional and gender-sensitive treatment for delinquent girls -- The nature of women's crime -- Women in prison -- Gender-sensitive programming within institutional settings -- Counseling the female offender -- Teaching life skills and promoting healing